Introspection and Reflections on The Plague Through Literary Works Mustofa Bisri and Risda Nur Widia: Introspeksi dan Refleksi Menyoal Wabah Melalui karya Sastra Mustofa Bisri dan Risda Nur Widia - Saptawuryandari, Nurweni (Kibas Cenderawasih, 2023)
Disasters in the formof plagues or pandemics, for example in human life, are problems that are not easily accepted because they cause worry and anxiety. The outbreak of the Covid-19 pandemic throughout the universe in the world, including Indonesia, has also caused endless anxiety and worry. Various print and electronic mass media discussed the pandemic, including Indonesian literati. Related to that, the discourse of plague became a realm to be explored in the creative space of the creation of literary works, in this case short stories.  Mustofa Bisri or Gus Mus and Risda Nur Widia wrote a short story entitled "Plague". The short story of the same name reveals how the plague suddenly appeared in human life.  Thepurpose of this study  is to  see how the plague is represented through the short story "Plague".  The method used is descriptive qualitative, which exposes writings based on the content of literary works that are associated with the socio-cultural environment.  This is in line with Laurenson and Singewood through Endraswara that literature is a social document in which it is a reflection of the situation at the time the literary work was written.  The findings show through the short story "Plague", how the author reveals the plague that suddenly appeared in the community can be regarded as introspection and reflection and how to anticipate so that the outbreak does not spread too widely to the community.